Decision support tools for efficient irrigation and resilience of olive trees - Kharrou, Mohamed Hakim; Ezzahar, Jamal; Er-Raki, Salah; Khabba, Said; Amazirh, Abdelhakim; Ait Hssain, Bouchra; Bouras, El Houssaine; Bousset, Jerome; Chehbouni, Abdelghani (International Center for Agricultural Research in the Dry Areas, 2024)
The Mediterranean basin represent over 90% of global olive tree area. The olive sector has been severely affected by drought in Morocco in the past few years and climate adaptation of olive orchard systems is a priority action withing the national climate strategies of Morocco (NAPA, NDC). This ClimBeR report, under the cross-scale climate and water resilience policy pathways, presents evidence from experiments and science-practice-policy dialogues between scientists, farmers and agriculture & water decisionmakers, conducted in the Marrakech region, in Morocco on different irrigation innovations. This transdisciplinary climate resilience research aims at improving climate-smart irrigation decisions for the olive orchard system across scales.